SERUM BILIRUBIN AND ANTIOXIDANT LEVELS IN FIRST DEGREE RELATIVES OF PATIENTS WITH ISCHEMIC HEART DISEASE AND NORMAL SUBJECTS - Mahmood, Nadia; Naseem, Tahira; Mukhtar, Farhana; Basheer, Rubina (Journal of Ayub Medical College Abbottabad, 2011)
Background: Coronary diseases appear to result from an overbalance between radical-generating, compared with radical-scavenging systems, a condition called as oxidative stress. Total antioxidant status (TAS) in human plasma reflects the balance between oxidants and antioxidants in each system. Bilirubin has been considered an antioxidant, with capacity to remove reactive species of oxygen. Present study tried to measure the total antioxidant status of first degree relatives of patients with IHD. Study also tried to evaluate the prognostic role of serum bilirubin in disease prevention or progression. Methods: Seventy five apparently healthy subjects in age group 20-50 years, comprising equal number of males and females, who were first degree relatives of ischemic heart disease patients, were included in the study. Family members were divided on the bases of their numbers, i.e., one family member (Group-A), 2 family members (Group-B) and more than 3 family members (Group-C). Study was cross sectional and carried out in a period of 6 months (Jun 2008-Jan 2009). Subjects with letter of consent were taken from general population. Seventy five healthy age matched people with no history of ischemic heart disease in family were taken as control. An overnight fasting blood sample was taken. Total antioxidant status was determined using a commercially available kit. Serum bilirubin was estimated by auto analyzer. Results: Family history of ischemic heart disease with serum bilirubin showed a significant negative correlation (p<0.05). But the values of TAS failed to show any significant correlation with the family history. It was observed that the value of serum bilirubin was decreased significantly (p<0.05) with an increased number of family members. Total antioxidant status failed to show any significant difference among all the three groups. Conclusion: Our data demonstrated that reduced serum levels of bilirubin were seen in people with a higher prevalence of coronary artery disease in the family. The levels of serum bilirubin showed a downward trend with an increase in number of family members affected with ischemic heart disease. Present study failed to show a definite association of total antioxidant status with family history of ischemic heart disease. Additional studies are still necessary on large number of first degree relatives to confirm and demonstrate the association of these findings with clinical outcomes. Keywords: Ischemic heart disease, first degree relatives, total antioxidant status and bilirubin